Studi tentang Perbedaan Evaluasi Etis, Intensi Etis (Etical Intention) dan Orientasi Etis dilihat dari Gender dan Disiplin Ilmu: Potensi Rekruitment Staf Profesional pada Kantor Akuntan Publik - Siti Mutmainah (The Indonesian Journal of Accounting Research, 2013)
This study tests for gender and discipline-based differences in ethical evaluation, ethical intentions and ethical orientation among subjects from accountancy department, faculty of law and information technology undergraduates, both women and men. Examination conducted with Mancova.The results indicate the difference in ethical orientation between women and men only occurred at moral construct of utilitarianism. There are no differences in ethical intention and ethical evaluation between men and women. Thus, in general research findings support structural approach.  The difference in ethical orientation also occurred among various subjects from different academic disciplines, especially in moral construct of justice, egoism and  deontological. There are also differences in ethical evaluation and ethical intention among subjects from different science disciplines.